Laser-induced breakdown spectroscopy for quantitative and qualitative analysis of the ash fusion temperatures of coal in power plants. Issue 3 (20th January 2021) - Zhang, Wenhao; Zhuo, Zhuang; Lu, Peng; Lu, Jingqi; Sun, Tengfei; Tang, Jing; Tang, Hailong; Zhou, Tao; Li, Li
Abstract : Prediction of coal ash fusion temperatures by LIBS with generalized spectral variables using coal rather than coal ash. Abstract : The prediction of coal fusion characteristics and determination of slagging behaviour are of great significance to the operation of thermal power plants. The traditional method needs a long time to measure coal ash fusion temperatures (AFTs) by heating the coal ash cone. The purpose of this work is to predict the coal AFTs directly from coal rather than coal ash using Laser-Induced Breakdown Spectroscopy (LIBS). On the premise that ash content, volatile matter, fixed carbon and moisture are known on the air-dry base state, these four parameters are added into the model as generalized spectral (GS) variables to improve the accuracy of coal AFT prediction, in which the R 2 of softening temperature (ST) and hemisphere temperature (HT) reached 0.9958 and 0.9856, the root-mean-square of cross-validation (RMSECV) reached 4.88 °C and 9.11 °C, and the root-mean-square of prediction (RMSEP) reached 8.15 °C and 11.3 °C, respectively. The trend relationships between the AFTs and the intensities (or ratio) of the spectral lines corresponding to individual elements of the LIBS spectrum were analysed. Then the variation trend of coal AFTs with specific element content (or ratio) is deduced qualitatively. We demonstrated that the model and scheme developed in this work can be applied in a real-time guiding role in the actual production process of the power plant.